Novel Development of an NbC‐Containing Powder‐Metallurgical Martensitic Steel with Outstanding Tribocorrosion Resistance. Issue 4 (18th October 2022) - Hahn, Isabel; Siebert, Sabine; Fluch, Rainer; Theisen, Werner; Weber, Sebastian
Abstract : The development of NbC‐containing martensitic stainless steels has made it possible to unite the properties of high corrosion resistance and wear resistance. If NbC is used as a hard phase instead of chromium carbide, the abrasive wear resistance of the steels is increased due to the greater hardness of NbC. The solubility of chromium in NbC is low. For this reason, chromium is fully available to form a passive surface layer to increase the corrosion resistance. In the steel melt, niobium leads to the formation of primary NbC, which grows very rapidly. Atomization of PM steels leads to the formation of coarse primary hard phases that clog the nozzle. Therefore, until now, steels with NbC as a hard phase are produced using the PM route with so‐called diffusion alloying; however, this production route is very complex and expensive. Herein, a novel Nb‐rich MC‐containing wear‐ and corrosion‐resistant steel that is produced using the usual PM route is presented. This steel consists of a martensitic matrix with evenly dispersed Nb‐rich MC having a volume of 2.5%. Due to the high hardness (>750 HV30) in combination with high resistance to pitting corrosion, the steel exhibits outstanding tribocorrosion resistance in 0.9% NaCl solution. Abstract : Herein, the tribocorrosion behavior of a novel powder‐metallurgical NbC‐containing steel from computer‐aided development is investigated. The steel exhibits excellent tribocorrosion resistance due to its microstructure. The fine dispersion of Nb‐rich MC supports the metal matrix against wear, and a fine distribution of the elements chromium, molybdenum, and nitrogen in the metal matrix increases the corrosion resistance of the steel.